Corchorus olitorius L. ameliorates alcoholic liver disease by regulating gut-liver axis. (October 2021) - Do, Moon Ho; Lee, Hyun Hee L.; Kim, Yoonsook; Lee, Hye-Bin; Lee, Eunjung; Park, Jae Ho; Park, Ho-Young
Graphical abstract: Highlights: Water-soluble extract from molokhia leaves (WM) were extracted and characterized. WM ameliorates alcohol-induced metabolic disorder parameters. WM ameliorates alcohol-induced inflammation and lipid accumulation in liver. WM regulates gut microbial composition and ameliorates gut barrier function. Abstract: Gut microbial dysbiosis, induced by alcohol consumption, disrupts the gut-liver axis, leading to the development and progression of alcoholic liver disease. In this study, we investigated the protective effects of the water-soluble extract from molokhia ( Corchorus olitorius L.) leaves (WM) on the alcohol-induced disruption of the gut-liver axis in mice. The administration of 50 and 100 mg/kg WM reduced the levels of serum biomarkers for liver injury. Moreover, WM treatment ameliorated the alcohol-induced increase in hepatic inflammation and lipogenic protein levels. WM improved the gut microbial composition disrupted by alcohol, which suggests the effects of WM in mediating the gut-liver axis. WM also improved gut barrier function via the regulation of gut permeability and tight junction protein expression. These results indicate that WM can be used as a food supplement to improve alcohol-induced liver damage by regulating the gut-liver axis.